2016
DOI: 10.1007/s10646-016-1720-0
|View full text |Cite
|
Sign up to set email alerts
|

A cost or a benefit? Counterintuitive effects of diet quality and cadmium in Lymnaea stagnalis

Abstract: Diet quality can have a strong impact on organismal fitness although diet quality is infrequently considered as a factor in toxicity tests. The purpose of this study was to assess how diets differing in nutritional content affect sensitivity to Cd as measured by several sublethal responses related directly to bioenergetics. We evaluated feeding rate, growth rate, behavior and macronutrient content in the pond snail Lymnaea stagnalis exposed to Cd and fed two different diets. Hatchlings were fed either lettuce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In the present study, the high‐calorie pellet and a combination of pellet and lettuce increased snail size (at least for the first 4 mo) compared to snails fed only lettuce. In a previous study (Reátegui‐Zirena et al ), L. stagnalis hatchlings fed pellets consumed as much as 3 times more food compared to snails fed lettuce, likely because the pellet was easier to ingest and assimilate. Herbivorous gastropods’ diet varies in cell wall toughness, palatability, nutritional value, and digestibility (Foster et al ); but more research is necessary before broad generalizations can be reached.…”
Section: Discussionmentioning
confidence: 87%
“…In the present study, the high‐calorie pellet and a combination of pellet and lettuce increased snail size (at least for the first 4 mo) compared to snails fed only lettuce. In a previous study (Reátegui‐Zirena et al ), L. stagnalis hatchlings fed pellets consumed as much as 3 times more food compared to snails fed lettuce, likely because the pellet was easier to ingest and assimilate. Herbivorous gastropods’ diet varies in cell wall toughness, palatability, nutritional value, and digestibility (Foster et al ); but more research is necessary before broad generalizations can be reached.…”
Section: Discussionmentioning
confidence: 87%
“…Many studies incorporate a single common and supposedly proven laboratory diet (e.g., studies following guidelines of the Organisation for Economic Co-operation and Development [OECD]); however, in nature animals rarely consume a single, specific food item throughout their lives (Madsen 1992;Zimmer et al 2012). More recently, Reategui-Zirena et al (2016) showed that the freshwater snail Lymnaea stagnalis was more sensitive to cadmium when fed a diet higher in nutritional content. Whereas diet quantity has been shown to alter chemical toxicity to a variety of aquatic organisms (Postma et al 1994), less is known regarding how differences in food quality impact toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…This type of dietary simplification is common in ecotoxicology but does not reflect the energetic and nutritive variety that many species in nature likely face, which may lead to additional uncertainties in extrapolating from laboratory to the field. Despite the obvious effects of dietary composition on growth and other fitness traits in snails (and other organisms), there are few studies that have explored how differences in diet quality translate to differences in toxicant sensitivity (see Reategui-Zirena et al 2016). Snails raised on different diets have shown significant differences in overall growth (Kimberly and Salice 2012;Sandland and Minchella 2003;Dorgelo et al 1995), susceptibility to parasitic infections (Sandland and Minchella 2003), and transgenerational chemical sensitivity (Plautz et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations